Bio-economic Model Predicts Economic Values for Beef Production - W. S. Leal; R. F. Costa; L. L. Cardoso; F. S. Mendonça; F. F. Cardoso; M. J. Yokoo; R. L. Weaber (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:The objective was to estimate economic values for production traits in a full life cycle system using a bio-economic model with Angus purebred and a terminal crossbreeding system with Nelore sires mated to Angus dams. Study Description:Phenotypic performance data were collected from the Bifequali crossbreeding scheme at the Embrapa Pecuária Sul Research Center of the Brazilian Agricultural Research Corporation. The data consisted of performance and carcass traits measured on progeny of Angus purebred and Nelore sires mated to Angus dams raised in a pasture-based production system from birth to slaughter (full life cycle). The economic characterization of the system was based on fixed costs and variable costs. The bio-economic was developed in ‘R’ programming language using the phenotypic information and the production costs. To estimate economic values, the bio-economic model was first parameterized and a base profit was calculated. The Bottom Line:The use of crossbreed animals provides an effective tool to improve important traits and system level profitability in a full life cycle beef production system.
Keywords: animal breeding; beef cattle; bio-economic model